THE ROLE OF MEDIA IN FAIR AND DEMOCRATIC ELECTIONS – THE PROBLEM OF A “FUNCTIONARY CAMPAIGN” IN SERBIA - Kovačević, Despot Đ (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2020)
The basic premise of free and fair elections is equal participation and representation of all candidates and candidate lists. Media are crucial in this process, taking into account they go hand in hand with modern democracies. As such, the role of media in promotional activities is regulated by law. The existing legal framework regulating election campaigns requires further improvements, especially in regard to participation of public officials in election campaigns and the use of public resources for these purposes. The engagement of public officials in election campaigns, or promotion, is defined as a “functionary campaign”. The year 2012 was a turning point for Serbia in terms of having functionary campaigns and consequently preventing free and fair elections. Until today multiple examples of usage of official capacities for campaign purposes have been reported. This paper defines functionary campaigns and analyses the existing legal provisions related to functionary campaigns in Serbia. While the legal framework requires further improvements what is worrisome is the poor implementation of the provisions in place. This paper also analyses the Government solutions proposed to the National Assembly of Serbia in 2019.
Keywords: functionary campaign; elections; electoral campaign; public officer